جودة نظم المعلومات الإدارية وأثرها على تحسين أداء العاملين دراسة ميدانية على العاملين في مصرف التجارة والتنمية وفروعه في مدينة بنغازي - أحمد عبدالسلام الشريف, هاجر (Dirasat in Economics and Business, 2026)
Management information systems are a fundamental element in improving job performance in organizations. Given the importance of this topic, the study problem revolved around the following question: “Is there an impact of management information systems on improving employee performance at the Bank of Commerce and Development in Benghazi?” The study aimed to determine the extent to which management information systems impact employee performance. The study population consisted of all employees at the Bank of Commerce and Development and its branches in Benghazi, numbering (405) employees in 2024. A simple random sampling method was used to determine the sample size, which amounted to (197) employees. (196) questionnaires were retrieved, and the number of questionnaires valid for analysis reached (195), representing (99%) of the total distributed questionnaires. To achieve the study objectives and analyze the collected data, the SPSS statistical program was used. The study reached a set of results, the most important of which are: • The level of implementation of management information systems and employee performance at the bank under study was high.